Las máscaras - PEREZ DE AYALA, Ramón (ESPASA CALPE ARGENTINA, 1940)
CONTENIDO : PEREZ GALDOS; VALLE-INCLAN; BENAVENTE; LINARES RIVAS; VILLAESPESA; MORANO; LOPE DE VEGA; SHAKESPEARE; IBSEN; WILDE, OSCAR; DON JUAN